A Rare Case of Classical Sweet Syndrome – Case Report - Anand, N.N.; Balaji, N.; Theja, V. Pranav; Vinodkrishna, Gopalagiri; Shanmuganandan, K. (Journal of Neonatal Surgery, 2025)
This case report presents a 30 year-old female who developed an acute febrile illness with painful, erythematous plaques over the left lower limb and right upper limb. A histopathological study revealed extensive neutrophilic infiltrates in the dermis, which is consistent with Sweet Syndrome. The patient responded favorably to systemic corticosteroid treatment, with the skin lesions and systemic symptoms cleared. This example shows the importance of detecting Sweet Syndrome, as well as the necessity for early diagnosis and fast treatment to reduce morbidity and potential consequences